2020
DOI: 10.1016/j.ympev.2020.106860
|View full text |Cite
|
Sign up to set email alerts
|

Cophylogenetic patterns in algal symbionts correlate with repeated symbiont switches during diversification and geographic expansion of lichen-forming fungi in the genus Sticta (Ascomycota, Peltigeraceae)

Abstract: patterns in algal symbionts correlate with repeated symbiont switches during diversification and geographic expansion of lichen-forming fungi in the genus Sticta (Ascomycota: Peltigeraceae), Molecular Phylogenetics and Evolution (2020), doi:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 85 publications
(103 reference statements)
2
20
0
Order By: Relevance
“…The fruticose lichen genus Stereocaulon may harbour thallus photobionts of either Asterochloris, Vulcanochloris or Chloroidium (Vančurová et al 2018). Species of Sticta may partner with chlorobionts of Symbiochloris, Coccomyxa, Elliptochloris, Heveochlorella or Chloroidium (Lindgren et al 2020). Squamulose Psora decipiens is reported to partner with either Asterochloris, Trebouxia, Chloroidium (Ruprecht et al 2014) or Myrmecia photobionts (Williams et al 2017;Moya et al 2018).…”
Section: Patterns Of Symbiont Pairingmentioning
confidence: 99%
See 1 more Smart Citation
“…The fruticose lichen genus Stereocaulon may harbour thallus photobionts of either Asterochloris, Vulcanochloris or Chloroidium (Vančurová et al 2018). Species of Sticta may partner with chlorobionts of Symbiochloris, Coccomyxa, Elliptochloris, Heveochlorella or Chloroidium (Lindgren et al 2020). Squamulose Psora decipiens is reported to partner with either Asterochloris, Trebouxia, Chloroidium (Ruprecht et al 2014) or Myrmecia photobionts (Williams et al 2017;Moya et al 2018).…”
Section: Patterns Of Symbiont Pairingmentioning
confidence: 99%
“…Soon thereafter, the 'trebouxioid' photobionts associated with foliicolous Gomphillaceae and Pilocarpaceae were also attributed to this genus (Sanders et al 2016). More recently, a study of Sticta lichens worldwide reported Heveochlorella to be the photobiont of numerous specimens from New Zealand and Indian Ocean islands, including six identified species and many undetermined collections (Lindgren et al 2020). In the opinion of Darienko & Pröschold (2019), the algae encompassed by Jaagichlorella, though distributed worldwide, are rare taxa.…”
Section: Elliptochloris Tschermak-woess -Like Its Sister Genusmentioning
confidence: 99%
“…Scale bars, 1 cm in (A); 0.5 mm in (B); 5 mm in (C,E,F); 0.1 mm in (D); and 50 µm in (G). Lindgren et al, 2020). During dispersal, the symbiotic partners can either disperse together within symbiotic propagules (Figure 1B) (vertical transmission), or the symbionts reproduce separately; for example, the mycobionts may produce ascospores in apothecia (Figure 1F) and re-establish the symbiotic association after dispersal (horizontal transmission).…”
Section: Introductionmentioning
confidence: 99%
“…A certain degree of symbiont specificity is a prerequisite for long-lasting symbiotic relationships. Within Lecanoromycetes (Ascomycota), the largest class of lichen-symbiotic fungi, most mycobionts seem to be highly specific in their choice of photobionts ( Dahlkild et al, 2001 ; Otálora et al, 2010 ; Dal Grande et al, 2014 ; Nyati et al, 2014 ; Leavitt et al, 2015 ; Chagnon et al, 2018 ; Jüriado et al, 2019 ; Dal Forno et al, 2020 ; Lindgren et al, 2020 ). During dispersal, the symbiotic partners can either disperse together within symbiotic propagules ( Figure 1B ) (vertical transmission), or the symbionts reproduce separately; for example, the mycobionts may produce ascospores in apothecia ( Figure 1F ) and re-establish the symbiotic association after dispersal (horizontal transmission).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent studies (e.g. Lindgren et al., 2020; Nelsen & Gargas, 2008; Piercey‐Normore, 2006; Zoller & Lutzoni, 2003) also found evidence for photobiont switching and sharing among mycobionts in various groups of lichens, but all indicated absence of strict co‐speciation. Therefore, although nearly 20,000 species of lichen‐forming fungi are known (Lücking et al., 2017), there appear to be far fewer species of photobionts, by around one to two orders of magnitude (Ahmadjian, 1967; Hill, 2009; Kroken & Taylor, 2000; Tschermak‐Woess, 1988).…”
Section: Introductionmentioning
confidence: 95%